Exploring Wettability of Re‐Entrant Microstructures: Effects of Geometry and Material Composition - Hoang Huy Vu; Nhat‐Khuong Nguyen; Pradip Singha; Glenn Walker; Nam‐Trung Nguyen; Navid Kashaninejad (Advanced Materials Interfaces)
Abstract This study systematically explores the wetting characteristics of re‐entrant microstructures, focusing on the interplay between the unique geometries and material compositions. While silicon dioxide (SiO₂) re‐entrant microstructures are previously studied, this research pioneers the fabrication of silicon carbide (SiC) re‐entrant microstructures. Through experimental approaches and theoretical analysis, the research assesses how variations in geometry and material impact wettability. Key findings reveal that SiC re‐entrant structures achieve an average contact angle of 145°, closely matching the 148° observed for SiO₂, indicating similar hydrophobic behavior. Although flat SiC surfaces exhibit higher inherent hydrophobicity than flat SiO₂ (59° vs 26° contact angle), re‐entrant geometry predominantly influences wetting behavior, overshadowing material differences. Structures with lower solid area fractions show increased hydrophobicity, with a distinct hierarchy: microlines are the least hydrophobic, followed by shark‐skin textures, rectangles, circles, and triangles. Additionally, increasing the gap size between structures enhanced hydrophobicity up to a critical point. This study paves the way for optimizing re‐entrant microstructures for specific applications, significantly enhancing the understanding of surface science and advancing material design.